Soil carbon saturation: a new model of soil organic matter stabilization and turnover - Stewart, Catherine E., author; Paustian, Keith H., advisor; Six, Johan, committee member; Conant, Richard T., committee member; Sutton, Sally, committee member (Colorado State University. Libraries, 2006)
The soil C saturation concept suggests an ultimate capacity of the soil to store C, dictating the rate and duration that soil may be effective in mitigating increasing atmospheric C02. This places a physicochemical limit on soil that is associated with textural, mineralogical and structural soil properties. This concept has been articulated in terms of four theoretical pools capable of C saturation: non-protected, physically- (micro-aggregate), chemically- (silt + clay), and biochemically-protected pools. My dissertation represents a multifaceted approach to examine C saturation in both whole soil and measurable soil fractions representing the four conceptual C pools. I evaluate the soil C saturation concept theoretically by modeling these relationships using published whole soil data, primary field data and through laboratory experiments. Analyses using published long-term soil C data from agroecosystem experiments suggested that within a given site, there was little support for models including C saturation, but when all sites were combined; there was strong support for the C saturation model. In general, published data were too sparse to adequately test individual sites. To evaluate the concept of C saturation for the four C pools, I used a three-part density, chemical, and physical fractionation scheme combined with modeling, using new data collected from eight agroecosystems in the US and Canada. I found that the chemically- and biochemically-protected pools showed strong evidence for C saturation, while the non-protected and physically-protected pools were non-saturating. In a 2.5 year laboratory experiment, I tested C stabilization rates and limits at two C addition rate to soils differing in soil C content and physicochemical characteristics. I found C saturation dynamics were most evident in the chemically-, biochemically- and some micro-aggregate protected C pools. I found greater C accumulation in the non-protected pool of the high C soil, suggesting C saturation of other pools. I conclude that SOC sequestration in many soils may be influenced by C saturation dynamics, impacting both decomposition kinetics and C stabilization. Soil C sequestration may be overestimated in models that do not account for C saturation dynamics.
Keywords: Soils -- Carbon content; Atmospheric carbon dioxide